Open Label Trial of the Tolerability and Efficacy of Zonisamide in the Treatment of Alcohol Dependence - Knapp, Clifford M. (Am J Drug Alcohol Abuse, 2010)
Objectives: The objectives of this study are to assess the tolerability and efficacy of the anticonvulsant zonisamide in an open label trial of the treatment of alcohol dependence. Methods: In this trial, zonisamide (400-mg daily) was administered to alcohol-dependent subjects (ADS) (n = 16) over 13 weeks. The mean daily consumption of standard alcoholic drinks and performance on a verbal fluency task, the COWAT, and on a measure of attention and visuomotor speed, the DSMT were assessed, and the occurrence of adverse events was monitored weekly. Results: The mean number of drinks consumed daily was significantly reduced from baseline levels during the treatment period. Performances on the COWAT and on the DSMT were not significantly reduced by zonisamide treatment. Overall, zonisamide was well tolerated by the study subjects. Conclusion: These results indicate that zonisamide administration may not impair verbal fluency in ADS, and are consistent with other studies that found zonisamide administration may reduce alcohol intake.